The Black Arts Movement Reprise: Television and Black Art in the 21st Century - Jeffrey O.G. Ogbar (European Journal of American Studies)
Beginning in the late 1960s, the Black Arts Movement grew as the cultural wing of the Black Power Movement. It was represented by a rich cross section of artistic work, often forged by young urban artists in genres as diverse as music, dance, visual arts, literature and theatre. No aesthetic was unaffected by inflections of this new black consciousness. This article explores the ways in which, a half-century after the Black Arts Movement, African Americans in television have cultivated an aesthetic and politics that resonate with the core thrust of the Black Arts Movement, one that sets black people in the center of their own cultural and political narratives, and inextricably bound to the wider movements of social justice in black communities.